The Norm of a Relation, Separating Functions, and Representations of Marked Quivers - Nazarova, L. A.; Roiter, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We consider numerical functions that characterize Dynkin schemes, Coxeter graphs, and tame marked quivers.